Digital maturity and corporate performance: The case of the Baltic states - Yulia Eremina; Natalja Lace; Julija Bistrova (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
Enterprise digitalization is a way for companies to make their processes more efficient, to enhance their marketing strategies, and improve their competitive moat within the global competitive landscape. To see how fast Baltic companies are adapting to digitalization trend and, therefore, how good they are at keeping or improving their competitive advantage, we have developed a digital maturity assessment methodology, which was applied to the listed enterprises in Estonia, Latvia, and Lithuania. This methodology allowed us to detect certain digital maturity trends, such as the significant growth of the attention paid towards concepts related to 'process automation'. Further, it was clear that many companies are concerned with online business, which can be well-seen from the analyzed annual reports. Additionally, we have compared the level and dynamics of the company's digital maturity to its financial and market performance. We have concluded that, although there is a positive relationship between several financial indicators (e.g., sales growth), it is too early to see the positive effect of digital maturity on a company's stock performance.
Keywords: 650; Baltic equity; corporate performance; digital maturity; digitalization; total return